Diagnostic efficacy and necessity of 18F-FDG PET/CT in fever of unknown origin: insights from a retrospective cohort study - Xiaoman Yu; Shuang Wang; Na Du; Hongguang Zhao; Haiying Chen (Frontiers in Medicine)
BackgroundDespite advancements in medical examination equipment and techniques, fever of unknown origin (FUO) remains challenging in internal medicine.PurposeThis study evaluates the diagnostic efficacy and necessity of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) in patients with FUO.MethodsWe retrospectively analyzed the results of 18F-FDG PET/CT in a cohort of 284 patients with FUO admitted to the Department of Infection at the First Hospital of Jilin University between January 2018 and March 2024. All patients received a final clinical diagnosis after various treatments, which helped determine the diagnostic relevance of identified lesions using 18F-FDG PET/CT. Additionally, univariate and multivariate logistic regression analyses were performed to evaluate the predictive value of relevant laboratory indices on the true-positive results of 18F-FDG PET/CT. The diagnostic performance for different etiologies of FUO was assessed by calculating the area under the receiver operating characteristic curve.ResultsOf the 284 enrolled patients, infectious diseases were diagnosed in 53 (18.7%), non-infectious inflammatory diseases in 76 (26.8%), malignant tumors in 66 (23.2%), and 89 (31.3%) remained undiagnosed. The final diagnoses of 136 patients (47.9%) correlated with their 18F-FDG PET/CT results, yielding a sensitivity of 79.5%, specificity of 61.1%, positive predictive value of 75.6%, and negative predictive value of 66.3%. Furthermore, a correlation was found between localized pain, prolonged activated partial thromboplastin time, and true-positive 18F-FDG PET/CT results.ConclusionThe high diagnostic efficacy of 18F-FDG PET/CT in FUO suggests its potential as a routine imaging modality, which could enhance patient management and reduce the need for costly and unnecessary invasive procedures. The identification of clinical factors that are predictive of true-positive diagnosis could facilitate more effective allocation of PET/CT imaging.